One new species and one new recorded species of the genus Kuzicus (Tettigoniidae: Meconematinae: Meconematini) from China - Zhu, Qi-Di; Shi, Fu-Ming (Zootaxa, 2017)
In this paper, a new species of the genus Kuzicus from China, Kuzicus (Kuzicus) leptocercus sp. nov., is described, with a new recorded species, Kuzicus (Kuzicus) koeppeli Sänger & Helfert, 2004 from China. The distribution data and morphological photographs of Kuzicus (Kuzicus) leptocercus sp. nov. and Kuzicus (Kuzicus) koeppeli Sänger & Helfert, 2004 are provided. All specimens are preserved in the Museum of Hebei University.